Treatment of Navicular Stress Fractures With an Algorithmic Approach. (January 2022) - Nunley, James A.; Green, Cynthia; Morash, Joel; Easley, Mark E.
Background: Navicular stress fractures are becoming increasingly more common. There is no universal consensus on treatment. We provide an algorithm that we feel will be useful in determining treatment. Methods: A retrospective study was performed on all patients having operative treatment of navicular stress fractures during a 10-year period. Acute fractures were treated with open reduction internal fixation. Chronic fractures greater than 3 months were treated with open reduction and internal fixation (ORIF) and iliac crest bone grafting. Chronic fractures with evidence of sclerosis, avascular changes, or those who failed previous surgery were treated with ORIF, iliac crest bone grafting, as well as vascular bone grafting. Patients' pain scores were recorded and a return-to-sports scale was used. Radiographic union was compared among the 3 groups using computed tomographic (CT) scans or radiographs. Results: Forty-three patients were identified. Fifteen received ORIF alone, 12 were treated with ORIF and bone graft, and 16 had ORIF with vascularized bone grafting. No difference was found among the median age of the 3 groups. In terms of radiographic healing, 3 patients in the ORIF group received radiographs alone. All other patients had follow-up CT scans. ORIF alone group had 80% union, ORIF with bone graft had 75% union, and ORIF with vascularized bone grafting had 100% union. Return to sports did not show any difference among the 3 groups. Conclusion: The algorithm dividing navicular stress fractures into 3 distinct groups with different operative techniques helped us address these difficult cases. Vascularized bone grafting certainly appeared to be beneficial for the more difficult cases. Level of Evidence: Level IV, case series.